A rare case of lingual thyroid with hyperthyroidism: A case report and review of the literature - Mattakarottu Joseph Jacob (Indian Journal of Endocrinology and Metabolism, 2012)
Lingual thyroid is a rare embryological anomaly resulting from failure of normal thyroid tissue to descend from the foramen cecum at base of tongue to its orthotopic location in front of the lower neck. It is a rare anomaly with a reported incidence of 1 in 3000 of the thyroid disorders. Lingual thyroid is often asymptomatic but may cause local symptoms such as dysphagia, dysphonia with stomatolalia, upper airway obstruction, and often with hypothyroidism. Hyperthyroidism is extremely rare finding and till now there are very few case reports published. We present here a case of lingual thyroid with hyperthyroidism, which was treated successfully with radioiodine.